2001
DOI: 10.1086/323353
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim‐Sulfamethoxazole (TMP‐SMZ) Dose Escalation versus Direct Rechallenge forPneumocystis CariniiPneumonia Prophylaxis in Human Immunodeficiency Virus–Infected Patients with Previous Adverse Reaction to TMP‐SMZ

Abstract: Trimethoprim-sulfamethoxazole (TMP-SMZ) is the most effective Pneumocystis carinii pneumonia (PCP) prophylactic agent, but adverse reactions are common among human immunodeficiency virus (HIV)-infected patients and limit its use. This randomized, double-blind controlled trial compared 2 methods of TMP-SMZ reintroduction, 6-day dose escalation and direct rechallenge, for PCP prophylaxis in HIV-infected patients who had experienced previous treatment-limiting reactions. The primary end point was the ability to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 30 publications
1
40
0
1
Order By: Relevance
“…Two studies compared the effectiveness of induction of tolerance versus rechallenge (single dose) in HIV-positive patients with documented reactions to TMP-SMX, and there were no differences in the success rates. 31,32 These results place into question the validity of previously reported induction of tolerance procedures that did not include a control group of patients who received full-dose TMP-SMX.…”
Section: Sulfonamidesmentioning
confidence: 73%
“…Two studies compared the effectiveness of induction of tolerance versus rechallenge (single dose) in HIV-positive patients with documented reactions to TMP-SMX, and there were no differences in the success rates. 31,32 These results place into question the validity of previously reported induction of tolerance procedures that did not include a control group of patients who received full-dose TMP-SMX.…”
Section: Sulfonamidesmentioning
confidence: 73%
“…Significantly, a large proportion of AALs were type A (23%), amendable to immediate "delabeling." In LTRs with a sulfonamide allergy, TMP-SMX or dapsone may also have been unnecessarily avoided if one considers that antibiotic sulfonamide cross-reactivity is lower than previously thought (5) and TMP-SMX desensitization or rechallenge is often effective (6,7).…”
mentioning
confidence: 99%
“…Because of the advantages of TMP-SMX, desensitization of patients who are intolerant of TMP-SMX has been used for many HIV-positive patients (1,17,51,100). Two randomized controlled trial have shown that gradually increasing in the dose of TMP-SMX improves the tolerability of the drug in HIV-positive patients (129).…”
Section: Trimethoprim-sulfamethoxazolementioning
confidence: 99%